PENGEMBANGAN PETA KONSEP BERBASIS NETWORK TREE SEBAGAI UPAYA PENINGKATAN KONSENTRASI BELAJAR MATA PELAJARAN IPS - Lailatul Rofiah; Wafiyatu Maslahah; Umi Maghfiroh (Jurnal Education and Development, 2023)
The research conducted by researchers is aimed at the use of the concept map media in social studies subjects at SMPI Diponegoro Wagir has several shortcomings, because the use of concept map media is considered less attractive, namely by drawing the concept map points on the blackboard without any pictures and Therefore, from the analysis of these constraints and problems, the researcher wanted to examine whether the development of a network tree-based concept map could solve the problems above and whether it can make students more concentrated in the ongoing social studies learning process. The design used adopts the ADDIE design model (Analysis, Design, Development, Implementation, Evaluation). This development product is in the form of a networktree-based concept map media that has gone through a validation process, namely 100% media experts, 100% material experts, and 100% questionnaire validators. The results of the student responses obtained In the student response questionnaire to the previous method obtained a score of 1353 with a percentage of 83.5% can be categorized as "quite valid". Meanwhile, in the student response questionnaire to the network tree-based concept map method, students obtained a score of 1402 with a percentage of 91,0% which could be categorized as "very valid". Based on the analysis carried out, it shows that there is an increase in student concentration after using the concept map method based on network tree, students can focus on one thing by putting aside other things that are not related. Researchers suggest teachers and researchers to continue to develop concept maps based on network tree because the material developed in this study is still very limited.